Wenckebach responsive to cephalosporins – it must be Lyme carditis - Lauren B. Dobbs; Marc A. Mugmon (Journal of Community Hospital Internal Medicine Perspectives, 2013)
A 37-year-old female presented to the hospital with erythema migrans and fatigue developed hypotension and variable episodes of AV block, including both Mobitz I and complete AV block. She was treated with IV antibiotics and her arrhythmia resolved within 24 hours without any further intervention.